A validation study of the Facial-Oral Tract Therapy Swallowing Assessment of Saliva. (April 2016) - Mortensen, Jesper; Jensen, Ditte; Kjaersgaard, Annette
Objective: To investigate the validity and reliability of the Swallowing Assessment of Saliva in detection of aspiration risk. Design: Validation study. Setting: Inpatient neurorehabilitation centre. Subjects: Adult patients with acquired brain injury. A total of 43 patients for concurrent validity and 33 other patients for inter-rater reliability. Interventions: Concurrent validity was established with blinded Swallowing Assessment of Saliva and endoscopic evaluation within a 24-hour time interval. Inter-rater reliability was established with two blinded Swallowing Assessments of Saliva within a one-hour time interval. Main measures: The Swallowing Assessment of Saliva is a seven-item scale with a combination of swallowing and non-swallowing items. It is based on the Facial-Oral Tract Therapy approach. Results: The Swallowing Assessment of Saliva had a sensitivity of 91%, 95% confidence interval (CI) (59; 100), a specificity of 88% %, 95% CI (71; 97) and a kappa coefficient of 0.87 ±0.17 in detection of aspiration risk. Furthermore, analyses showed that experienced and inexperienced occupational therapists performed equally in detection of aspiration risk. Conclusion: The Swallowing Assessment of Saliva is a simple, sensitive and reliable assessment for detecting aspiration risk in patients with acquired brain injury.